On Literary Spoils of War in Private Libraries. The Case of Rålamb at Länna Gård - Peter Sjökvist (Biblioteka)
After arriving in Sweden, the literary spoils of war taken from Poznań in the Swedish deluge in the 1650s ended up in the private country house library of nobleman Clas Rålamb (1622–1698), who had been sent by Swedish King Charles X Gustavus (reigned 1654–1660) to manage the difficult situation in this Polish town while it was under Swedish command. With the help of a still extant inventory from the 1690s drawn up at the country house before the books were donated to Uppsala University Library, where they remain today, the contents and possible arrangement of this library are briefly described and discussed in this article. Some notable characteristics are the sections on theology and duplicates being larger than what would normally be expected from a country house library of this kind. It is assumed that these factors, among others, indicate that Rålamb did not make any sort of selection when seizing the books from monasteries and churches in Poznań. In addition, it suggests that their primary role in their new environment was to increase the cultural capital of their owner. Large numbers of the confessionally Catholic books were of little practical use in a Sweden characterized by Lutheran Orthodoxy.